Finding the jigsaw piece for our jigsaw puzzle with corporate social responsibility: the impact of CSR on prospective applicants’ responses - Duarte, A.P. (2014)
Purpose – This study aims to examine the influence of different corporate social responsibility (CSR) dimensions on prospective applicants’ responses, namely, organizational attractiveness and intention to apply for a job vacancy (IAJV). Design/methodology/approach – Using an experimental 2 × 3 crossed factorial design (n = 195), the level of engagement of a hypothetical company in socially responsible practices (high vs low) was manipulated concerning three dimensions of CSR (employees, community and environment and economic level). Participants were randomly assigned to one of the six conditions and, after reading the corresponding scenario, were asked to evaluate the extent to which the company was considered a good place to work and their IAJV in it. Findings – The level of engagement in socially responsible practices had a positive effect both on the degree to which participants favorably perceived the organization as a place to work and on their IAJV. Furthermore, the level of engagement in practices toward employees and in the economic domain had a stronger effect on participants’ responses than the engagement in practices that benefit community and environment. Research limitations/implications – Data were obtained in a laboratory setting, so the generalization of results to actual job search settings must be made with caution. Practical implications – CSR can be a source of competitive advantage in the recruitment of new employees. Because not all CSR dimensions have the same effect on applicants’ responses, companies should take into account the CSR dimensions in which they are engaged and communicate them to the public. Originality/value – As far as we know, this is the first study to examine the impact of different CSR dimensions both on organizational attractiveness and IAJV.